DAYAK CUSTOMARY PRACTICES FOR PREGNANT WOMEN OUT OF WEDLOCK IN SERUYAN REGENCY - Nor Harika; Abdul Khair; Sabarudin Ahmad (RADJA PUBLIKA, 2025)
Out-of-wedlock pregnancies in Seruyan Regency are stigmatised and punished according to customary law. This issue often leads to social exclusion, gossip, forced marriages, and the obligation to pay singers as a customary sanction for allegedly violating morals and traditional norms. The aim of this study is to investigate the imposition of singers on women with out-of-wedlock pregnancies and its impact on their social and psychological lives. This research was conducted through an empirical approach involving participatory observation, literature study, and semi-structured interview methods. The results indicate that customer singers are more social and informal, and women experience greater stigma. Among the effects that arise are the loss of the right to choose a partner, neglect within marriage, delay in education, and expulsion from the community. The community views this as a way to preserve family dignity and village reputation however, the implementation of sanctions tends to contradict